2007
DOI: 10.1002/jnr.21585
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation: A new candidate in modulating adult neurogenesis

Abstract: Any pathological perturbation to the brain provokes a cascade of molecular and cellular events, which manifests in the form of microglial activation and release of various proinflammatory molecules. This eventually culminates in a profound neuroinflammatory reaction that characterizes the brain's response to stress, injury, or infection. The inflammatory cascade is an attempt by the system to eliminate the challenge imposed on the brain, clear the system of the dead and damaged neurons, and rescue the normal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(149 citation statements)
references
References 91 publications
3
145
0
1
Order By: Relevance
“…In normal conditions it promotes and regulates neurogenesis [61], plays a role in hippocampal development [29], and is essential to learning and memory formation [28,62] (Figure 2, Table 1). This complex and divergent role of TNF-α is mediated is required for cognition at moderate levels by aiding hippocampal development and synaptic signalling.…”
Section: Translational Neurosciencementioning
confidence: 99%
“…In normal conditions it promotes and regulates neurogenesis [61], plays a role in hippocampal development [29], and is essential to learning and memory formation [28,62] (Figure 2, Table 1). This complex and divergent role of TNF-α is mediated is required for cognition at moderate levels by aiding hippocampal development and synaptic signalling.…”
Section: Translational Neurosciencementioning
confidence: 99%
“…Both isoenzymes convert arachidonic acid into multifunctional prostanoids. COX-2 enzyme is reported as a key player [11] in neuro-inflammation which is involved in most neurodegenerative disorders by eliciting neuronal death and influencing formation of new neurons [9]. In several tissues, mRNA level of COX-2 was studied and level in the brain was lowest [24], but its expression in brain was not the lowest [35].…”
mentioning
confidence: 99%
“…Recent data have also supported the idea that a reduction in the levels of anti-inflammatory factors itself can further enhance vulnerability of dopaminergic neurons to apoptosis in a neurodegenerative environment (Barnum and Tansey, 2010;Lu et al, 2010;Maguire-Zeiss and Federoff, 2010). Furthermore, it has been recently suggested that pro-inflammatory cytokines exert a negative impact on neuronal differentiation, while anti-inflammatory cytokines facilitate neurogenesis (Mathieu et al, 2010) and neuronal migration towards appropriate targets (Das and Basu, 2008). These data clearly indicate that pro-and antiinflammatory responses must be strictly balanced to prevent the potential detrimental effects of prolonged or unregulated inflammation on vulnerable neuronal populations .…”
Section: Stem Cell and Neuroinflammationmentioning
confidence: 88%